2001
DOI: 10.1046/j.1365-2036.2001.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between low‐dose ranitidine and antacid in decreasing gastric and oesophageal acidity and relieving meal‐induced heartburn

Abstract: Determining integrated gastric and oesophageal acidity provides novel information regarding the pathophysiology of meal-induced heartburn as well as the actions of low-dose ranitidine and antacid. For subjects with meal-induced heartburn, treatment with low-dose ranitidine plus antacid is particularly effective in decreasing gastric and oesophageal acidity as well as heartburn severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…However, the currently available therapeutic modalities are not fast or effective enough to provide good control of postprandial heartburn. [26][27][28][29][30] In patients who consume antireflux medications only in response to acute heartburn, PPIs appear to have no value due to the time required to reach maximum efficacy. Consequently, PPIs are not considered a good therapeutic option for postprandial heartburn, leaving patients to utilize compounds such as antacids, Gaviscon, sucralfate, or H2RAs.…”
Section: Postprandial Heartburnmentioning
confidence: 99%
“…However, the currently available therapeutic modalities are not fast or effective enough to provide good control of postprandial heartburn. [26][27][28][29][30] In patients who consume antireflux medications only in response to acute heartburn, PPIs appear to have no value due to the time required to reach maximum efficacy. Consequently, PPIs are not considered a good therapeutic option for postprandial heartburn, leaving patients to utilize compounds such as antacids, Gaviscon, sucralfate, or H2RAs.…”
Section: Postprandial Heartburnmentioning
confidence: 99%
“…The perception of heartburn serves as a trigger for medication use, and the expectation is an immediate symptom relief that PPIs are unlikely to provide. The onset of action of antacids on esophageal acid concentration is 30 min after dosing and inhibition persists for 1 h 65 . However, studies reported that meaningful heartburn relief can already be achieved 19 min after consumption 66 .…”
Section: Statementsmentioning
confidence: 99%
“…When consumed 30 min prior to a meal, H 2 RAs are effective in completely or partially preventing postprandial heartburn 68 . There is some evidence to suggest that simultaneous consumption of both an H 2 RA and an antacid provides better control of esophageal acid exposure and heartburn symptoms, when compared to the clinical effect of each one of these products alone 65 . On‐demand treatment with H 2 RAs has been shown to be safe and effective in GERD patients.…”
Section: Statementsmentioning
confidence: 99%
“…Because cisapride had been reported previously to relieve heartburn, [11][12][13]16 we examined its effects on oesophageal and gastric pH and heartburn severity following a meal that has been found previously to induce heartburn in susceptible subjects. 25 The present report is based on results from a two-way crossover study of placebo and 10 mg cisapride administered with 65 mL of water 30 min before the start of the meal. This study was conducted during September and October 1998 -before cisapride was withdrawn for prescription use in humans.…”
Section: Methodsmentioning
confidence: 99%